THE IMPLEMENTATION OF CLT (COMMUNICATIVE LANGUAGE TEACHING) TO IMPROVE PUPILS’ SPEAKING ABILITY - Abdul Rabbi Arrasul; Nabilla H. Pole (BABASAL English Education Journal, 2021)
The purpose of this research was to determine wheter using CLT (Communicative Language Teaching) can improve pupils’ speaking ability at Prateepsat Ismail Memorial School or not. This research used a quasi-experimental research that required a pre-test and a post-test for both groups. The research population was pupils in grade 2, where class 2/2 as an experimental class consisiting of 36 pupils and class 2/1 as a control class consisting of 36 pupils. In collecting data, reseracers used test. The test consisted of a pre-test and post-test. Data were analyzed statistically. After being analyzed, the result of t-counted was 11,977 with 70 degrees of freedom and a significance level of 0,05, the table is 1,666. This research used a significance level of 0,05 because it has moderate accuracy. Therefore the result of t-counted is higher than t-table. It means that the hypothesis of this research is accepted. In conclusion, there was a significant effect in using CLT (Communicative Language Teaching) to improve pupils’ speaking ability of the second grade at Prateepsat Ismail Memorial School, Thailand.